VISCOSITIES OF TRIGLYCERIDES IN A VARIETY OF SOLVENTS - SINNASAMI, RAVIN (IRC, 2017)
Due to the increase in demands and production of petroleum-based fuels, the currently available reservoir of petroleum-based are ever so diminishing. This has led to an increase in researches focusing on alternative fuel source. The predominant research in this area is focused on biodiesel. Although there has been an increase in the number of researches that focuses on biodiesel, those researches are most commonly focused on increasing the total yield in transesterification process. The method to achieve that is by using a co-solvent in the transesterification process. While the usage of co-solvent increases the total yield of the transesterification process, this project attempts to learn about the viscosity of triglycerides in solvent. This is done in order to understand the effect of using solvent upon the size of the triglycerides and the intermolecular interactions of the triglycerides molecules. The size of triglycerides and the intermolecular interactions may vary with the type of solvent used. Hence, in this project, the viscosity of the triglycerides in various solvent will be measured and from that, the size of the triglycerides molecules and intermolecular interactions can be calculated. The resulting information can be used to compare the hydrodynamic size and intermolecular interaction across different solvents.